NEODYMIUM ISOTOPES IN BASALTS OF THE SOUTHWEST BASIN AND RANGE AND LITHOSPHERIC THINNING DURING CONTINENTAL EXTENSION - DePaolo D.J.; Daley E.E. (My University, 2000)
The chemical compositions, ages, and Nd and Sr isotopic compositions of Miocene basaltic volcanic rocks from the southwestern Basin and Range Province were measured. The data presented, and other data obtained from the literature show that temporal variations in the Nd and Sr isotopic compositions are typically correlated with the timing of local crustal extension. The isotopic variations cannot be accounted for by crustal contamination, and are best interpreted as indicating the involvement of subcontinental lithospheric mantle as a major source of basalt magma before and during the early stages of extension, giving way to asthenospheric sources as extension proceeds. It is inferred that the basalt isotopic and age data provide information about the amount and timing of changes of the overall lithosphere thickness during extension. If this inference is valid, the inferred lithosphere thickness vs. time histories can be compared to the amount and timing of upper crustal extension to evaluate competing models for lithospheric strain during continental extension.The depth of the lithosphere-asthenospshere boundary is inferred primarily from the isotopic data, but can be refined by accounting for differences in the depth of origin of the basalts as suggested by differences in the degree of silica saturation (nepheline normative vs. hypersthene normative). The transition between silica saturated and undersaturated magmas is dependent on many factors, but for the conditions likely to apply to the Basin and Range Miocene volcanism, it corresponds to a depth of origin of 50+/-10 km.The data presented show strong support for the inferred mantle geochemical stratigraphy, and the inferred modern depths to the lithosphere-asthenosphere boundary are consistent with available seismic refraction and structural data. In the highly extended regions near the eastern and western margins of the southwestern Basin and Range, temporal changes in basalt isotopic compositions indicate that the subjacent lithospheric mantle thinned contemporaneously with the upper crust, as would be predicted for pure shear. These areas are also characterized by relatively high (although still low) basalt extrusion rates. In contrast, upper crustal extension in the Death Valley area was not accompanied by significant thinning of the subjacent lithospheric mantle, which implies that the location of lithospheric thinning was offset from the location of upper crustal extension as in a simple shear model. The total amount of lithospheric thinning is generally less than would be expected from the magnitude of upper crustal extension and is more evenly distributed; this suggests that there is also a component of distributed shear.
Keywords: ISOTOPES; BASALTS; LITHOSPHERIC THINNING